The Role of Educational Leaders in Strategic Planning at the Secondary Level in Karachi, Pakistan - Muhammad Nadeem; Ahmad Shaheen, Dr. Fayyaz (JELM, 2025)
The approach for the study was descriptive to describe the role of educational leaders in strategic planning and explore the influencing factors in the implementation of strategic planning. The qualitative research design of semi-structure interviews was employed to meet the objectives of the study. Research was made by researcher under supervision, consist of 16 items. The population of the study was all educational leaders of Karachi and sample size was 12 educational leaders from government and private secondary schools in equal proportion. Thematic analysis using inductive approach was done to analyzed the transcripts of interviews and their frequencies converted into descriptive words. 16 themes magnified in analysis and was related to leader’s role and influencing factors equally. The study summarized the role of leaders in strategic planning and explored the influencing factors in strategic planning. It was concluded that the leaders have vital role in establish educational goals and communication strategies with stake-holders, and social skills and emotional management, considering of cultural value, national education policy and engagement of stake-holders in whole process are influencing factors in implementation of strategic planning. At the end the suggestions were given to educational leaders, policy makes, teaching and learning community, and future research to explore more about strategic planning at secondary level of education.